Epidemiologic study of 80 patients with ulcerative colitis referred to Imam Hospital in Ardabil city during 2004-2011 - Sadeghifard, Vahid; Amani, Firouz; Amani, Firouz; Avesta, Leili; Avesta, Leili (International Journal of Research in Medical Sciences, 2017)
Background:Ulcerative colitis is one of the inflammatory bowel diseases with unknown etiology. Genetic and environmental factors are thought to be effective in this disease. The aim of this study is to assessment of demographic features and clinical symptoms of ulcerative colitis patients refereed to Emam hospital in Ardabil city. Methods:In this retrospective cross-sectional study, 80 cases of ulcerative colitis referred to Emam hospital in Ardabil city were evaluated during 2004-2011. The diagnosis was confirmed based on clinical features, colonoscopy, and pathology and resulting of other causes. Data were collected through direct interview and analyzed by statistical method in SPSS software. Results:Mean age of patients was 36.4 (SD=18.4). Duration of symptoms onset until diagnosis was 8 months. Male to female ratio was 0.8/1. 38(47.5%) of patients were male and 42 (52.5%) were female. 3 (3.75%) of patients have history of positive UC and 4 (5%) history of appendectomy. According to colonoscopy finding, 1 (1.25%) have rectum involvement, 27 (33.75%) recto sigmoid, 23 (28.75%) left side colon and 4 (5%) have pan colitis. Conclusion:Results showed that in compare with other places, clinical signs of ulcerative colitis in Ardabil province are different and so doing other d epidemiologic studies based on population to determine incidence and prevalence ulcerative colitis in Ardabil province is necessary.